2020
DOI: 10.4314/sajas.v50i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Defatted yellow mealworm larvae (<I>Tenebrio molitor</I> l.) meal as possible alternative to fish meal in quail diets

Abstract: The effects of replacing fish meal (FM) in the diet with defatted mealworm larvae meal (DMLM) on growth, carcass, and biochemical constituents of serum of Japanese quail chicks were investigated. A total of 600 unsexed one-day-old chicks were allotted to five dietary treatments with six replicates of 20 chicks each. The diets were formulated by replacing FM with DMLM at the levels of 25% (D25), 50% (D50), 75% (D75), and 100% (D100). The FM, D25 and D50 diets resulted in greater final bodyweight, higher bodywei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The inclusion of TM larvae meal in the diet of JQ provided satisfactory results in terms of carcass traits and cooking losses being comparable to the those obtained in the C group. Despite authors recently reporting that TM inclusion at 3 g 100 g −1 did not negatively affect the carcass weight of JQ, 12,14 others found that TM defatted larvae meal included at 2.3, 3.5 or 4.6 g 100 g −1 (DM basis) produced a detrimental effect on the carcass weight 13 due to the significant heavier small intestine and abdominal fat compared to the control and the group fed TM at 1.1 g 100 g −1 (DM basis). Colour is one of the main qualitative aspects that can influence food acceptance by consumers, and it is frequently used as an indicator of food's economic value.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The inclusion of TM larvae meal in the diet of JQ provided satisfactory results in terms of carcass traits and cooking losses being comparable to the those obtained in the C group. Despite authors recently reporting that TM inclusion at 3 g 100 g −1 did not negatively affect the carcass weight of JQ, 12,14 others found that TM defatted larvae meal included at 2.3, 3.5 or 4.6 g 100 g −1 (DM basis) produced a detrimental effect on the carcass weight 13 due to the significant heavier small intestine and abdominal fat compared to the control and the group fed TM at 1.1 g 100 g −1 (DM basis). Colour is one of the main qualitative aspects that can influence food acceptance by consumers, and it is frequently used as an indicator of food's economic value.…”
Section: Discussionmentioning
confidence: 90%
“…However, 18% of the overall European poultry production in 2021 (in total, 13 741 million tonnes) is represented by other avian species, such as turkey (Meleagris gallopavo), duck (Anas platyrhynchos domesticus), quail (Coturnix coturnix), pheasant (Phasianus colchicus) and partridge (Alectoris barbara). 7 Despite the fact that several of these species (such as turkey and quail) commonly eat insects in their natural diet, limited studies have been conducted on barbary partridge, 8,9 broiler Japanese quail, [10][11][12][13][14] laying Japanese quail, 15,16 and turkey. 17 Focusing on Japanese quail (JQ), increasing levels of dietary TM in diets up to 3 g 100 g −1 could improve quail body weight (BW), feed conversion ratio (FCR), carcass yield and jejunum morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Others authors have recently shown the in vitro cholesterol-binding capacity of mealworm flour, as well as that of other edible insects [ 35 ]. In vivo, T. molitor has been demonstrated to decrease the serum total cholesterol in quails and mandarin fish fed with different levels of this insect, suggesting a link between the potential hypocholesterolemic activity and chitin contained in the mealworm [ 36 , 37 , 38 ]. Further studies elucidating the compounds contained in the mealworm extract responsible for the potential hypocholesterolemic activity might be of interest in order to develop insect food products aimed at enhancing this effect.…”
Section: Resultsmentioning
confidence: 99%
“…IM chitin prevents the absorption of cholesterol and lipid by binding to anionic carboxyl groups of fat and bile acids in the intestine and connecting them to neutral lipids with hydrophobic bonds. Additionally, chitin increases the excretion of cholesterol and lipids in feces by inhibiting the reabsorption of bile cholesterol (Šimunek and Bartonová, 2005;Yildirim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%